Revisiting ‘the nature of Protestantism’: justification by faith five hundred years on - Zahl, Simeon (Wiley, 2018)
This essay is about the state of the doctrine of justification by faith alone today in light of recent critiques, and about the ways in which the doctrine continues to shape Protestants who no longer formally subscribe to it. The argument is first and foremost theological rather than historical, but it is driven by an interest in how evaluations of justification by faith have changed over time to get us where we are today. My hope is that a thoughtful evaluation of the current state of this doctrine as it looks from within the protestant fold will give us a some new insight into this important dimension of the relation between protestant and Catholic theological traditions, as we look back over 500 years of division. Ultimately, it will give us some new purchase on the old question of ‘the nature of Protestantism’ through analysis of a certain kind of orientation to psychological and affective realities in protestant theology.